INFLUENTIAL FACTORS IN SELECTING A BACHELOR’S DEGREE FROM INTERNATIONAL DEGREE PROGRAMMES OFFERED IN SRI LANKA: PERSPECTIVES OF LECTURERS AND GRADUATES (Proceedings of the International Conference on Education, 2018)
National University intake in Sri Lanka has become progressively competitive due to the limited number of opportunities available. Majority of the students who fail to enter National Universities and students who complete Advanced Level in British curriculum have been increasingly seeking alternative educational options in the domestic market. Of those students, a small percentage is presumed to continue their university level education (ULE) overseas based on affordability.  At present many private higher educational institutes (PHEI) in Sri Lanka offer various types of International Degree Programmes (IDPs) to cater to the rising demand of ULE. Due to the flexibility and optionality in IDPs offered in Sri Lanka, the decision making process in selecting a Bachelor’s degree (BD) in IDPs has become complex and multifactorial. This study aims to explore factors influencing students’ choice in selecting a BD from IDPs.  Data for the study were collected via focus group discussions with lecturers and graduates in randomly selected PHEIs. 62 themes which emerged in thematic analysis of data were categorized into 7 variables, namely, university characteristics, source of information (messenger), programme evaluation, cost, marketing strategy, location and infrastructure facilities. The percentage of occurrence of each theme has been calculated to identify how the lecturers and graduates have ranked the themes based on their level of importance. University characteristics, programme evaluation, infrastructure facilities and messenger were rated as most influential by lecturers and graduates, but with different orders of importance. ‘Cost’ is the least influential factor for lecturers while ‘location’ is for graduates.
Keywords: University Level Education; Students’ choice; Bachelor’s Degree; International Degree Programmes